2016
DOI: 10.3928/1081597x-20160728-02
|View full text |Cite
|
Sign up to set email alerts
|

Double-Pass Retina Point Imaging for the Evaluation of Optical Light Scatter, Retinal Image Quality, and Staging of Keratoconus

Abstract: Double-pass retina point imaging is useful in correlating retinal image quality with keratoconus severity. The OSI may represent a clinically significant parameter for staging keratoconus with a unique ability to directly evaluate quality of vision in this population. [J Refract Surg. 2016;32(11):760-765.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…ese results were consistent with those given by Ye et al [12], but they did not evaluate the OSI value. Leonard et al [13] compared the OSI values between the keratoconus eyes and normal eyes and found statistically significant increments of OSI scores in the AK1 and AK2 group, which was also consistent with our results. However, our results further showed the OSI had no significant difference between the FFK and normal group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ese results were consistent with those given by Ye et al [12], but they did not evaluate the OSI value. Leonard et al [13] compared the OSI values between the keratoconus eyes and normal eyes and found statistically significant increments of OSI scores in the AK1 and AK2 group, which was also consistent with our results. However, our results further showed the OSI had no significant difference between the FFK and normal group.…”
Section: Discussionsupporting
confidence: 93%
“…Ye et al [12] found that the modulation transfer function cutoff (MTF cutoff), Strehl ratio (SR), OQAS values at contrasts of 100% (OV-100), OQAS values at contrasts of 20% (OV- 20), and OQAS values at contrasts of 9% (OV-9) had significant differences between the normal and forme fruste keratoconus (FFK) patients. Leonard et al [13] reported that the OSI was increased in keratoconic eyes and could be considered as a clinically significant parameter to stage keratoconus by directly evaluating visual quality. However, to the best of our knowledge, comparisons of all the parameters among FFK, mild keratoconus, moderate keratoconus patients, and normal have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Forward light scatter detects the light that does not come into focus on the retina because of aberrations within the optical system, resulting in halos, glares, and difficulty during driving under scotopic conditions (8) . Double-pass retinal imaging (DPRI) can be used to analyze the point-spread function (PSF) directly from the retinal image; it is a validated and reproducible technology designed to evaluate forward light scatter through the optical system (9)(10)(11) . The method enables mathematical reconstruction of the entire optical system allowing the clinician to "see" images as they are cast onto the patient's retina and perceived by the patient (11) .…”
Section: Introductionmentioning
confidence: 99%
“…; Leonard et al. ). Further studies will analyse a larger number of patients with different patterns of scatter, especially posterior subcapsular and cortical cataracts, as well as in different corneal pathologies that cause scattering and age‐matched controls.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in the OSI has been observed in eyes with keratoconus (Leonard et al. ), and significant correlations have been found between the OSI and the logMAR in patients after corneal transplantation (Kamiya et al. ).…”
Section: Introductionmentioning
confidence: 98%